Fundamentals of public utilities management - Spellman, Frank R. (CRC Press, 2021)
"Fundamentals of Public Utilities Management provides practical information for constructing a roadmap for successful compliance with new and ever-changing regulatory frameworks, upgrading and maintenance, and general management of utilities operations. It describes current challenges faced by utility managers and offers best practices. In an effort to maximize the usefulness of the material for a broad audience, the text is written in a straightforward, user-friendly, conversational style for students and practicing professionals alike. Features : Presents numerous illustrative examples and case studies throughout, examines environmental compliance and how to best work with continually changing regulations, and frames the discussions in a context of energy conservation and ongoing sustainability efforts. Fundamentals of Public Utilities Management is designed to provide insight and valuable information to public utility sector managers and prospective managers in water operations (drinking water, wastewater, storm water), and to serves the needs of students, teachers, consulting engineers, and technical personnel in city, state, and federal public sectors"--